IDEAS FOR THE ORGANIZATION OF SCIENTIFIC RESEARCH IN PHYSICAL EDUCATION - Umbarov Djuraqul Musayevich (Galaxy International Interdisciplinary Research Journal, 2021)
This article is devoted to scientific research in order to achieve effective results in physical education and sports, to increase the impact of exercise on the body and the effective organization of the pedagogical process of physical education, to develop appropriate methods of physical education and sports. and the occurrence of theoretical, generalizing types.